Morphological errors in skills writing the requirement of the class vocational school of students Ceger private vocational schooleast Jakarta - Ila Nafilah; Reni Rokhayati; Yulia Agustin (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
Writing skills are one of four language skills, three of which are reading, listening andspeaking. Writing is a means of expressing ideas or ideas to communicate indirectly to others so thatthe person understands them. There are four types of essays, which are essays of description,argumentation, persuasion and narrative. This study uses a qualitative descriptive approach thatemphasizes the depth of appreciation of the interaction between concepts that are being studiedempirically using words or images. Research with this qualitative approach uses content analysismethod. The research method used to analyze the narrative essays is by using a qualitative methodthat focuses solely on morphological errors by examining the fields of affixation, reduplication,composition, and morphophonemic errors related to narrative essays of fifth grade students ofelementary school (SD). The purpose of this research is to analyze and obtain a clear picture ofmorphological errors in narrative essay writing skills of fifth grade elementary school students.Key Words: morphological errors, writing skills, narrative essays.